Extending the conversation over the immune-related hepatotoxicity: author response to Dr. Gauci et al. Issue 3 (18th March 2021) - Ziogas, Dimitrios C; Gogas, Helen
Abstract : Immune-related hepatotoxicity (IRH) remains the subject of many immune-oncology debates due to its challenging diagnosis and management. Although it is currently defined by the restrictive Common Terminology Criteria for Adverse Events (CTCAE), the term of IRH covers a wide range of liver pathologies, including hepatitic, cholangitic, mixed, steatotic and nonspecific patterns of injury. Even when liver biopsy is performed, the recognized histopathological findings cannot predict the response to steroids or the need for secondary immunosuppression, and usually do not significantly modify the suggested empirical treatment of IRH. Beyond the CTCAE grading, a more comprehensive assessment of IRH severity, including laboratory biomarkers and clinical features, should be developed and a more patient-oriented management should be established by additional randomized evidence, incorporating hepatology and immune-oncology experience.